A high-strength M2B type high-entropy alloyed boride ceramic and its preparation method
A high-strength M2B type high-entropy alloyed boride ceramic with Fe, Co, Ni, and B composition, prepared via vacuum arc melting, addresses mechanical and oxidation limitations, achieving superior mechanical properties and resistance in extreme environments.
Patent Information
- Application Number
- CN202310969543.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-08-03
AI Technical Summary
Traditional high-temperature alloys and boride-based ultra-high temperature ceramics face limitations in mechanical properties and oxidation resistance due to strong covalent bonds and oxygen impurities, restricting their use in extreme environments.
A high-strength M2B type high-entropy alloyed boride ceramic composed of Fe, Co, Ni, and B with a 1.0:1.0:1.0:2.0 atomic ratio, prepared through vacuum arc melting to achieve a stable tetragonal phase, enhancing density and oxidation resistance.
The M2B-type high-entropy alloyed boride ceramic exhibits high-temperature oxidation resistance, compactness, and excellent mechanical properties, avoiding impurities and porosity issues common in other preparation methods.
Smart Images

Figure CN116770149B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-temperature alloy materials, and specifically relates to a high-strength M2B type high-entropy alloyed boride ceramic and a preparation method thereof. Background Art
[0002] At present, the performance requirements for high-temperature structural materials in the fields of aerospace, nuclear power, energy conversion, etc. are constantly increasing. The service temperature of single-crystal nickel-based high-temperature alloys has reached 1150℃, approaching its melting point. The performance development has reached the limit of the material, and new high-temperature alloy materials are urgently needed to be designed. Traditional metal materials usually use one or two metal elements as the main components, and introduce a small amount of alloying elements to improve their comprehensive mechanical properties. In 2004, the concept of multi-principal high-entropy alloys was proposed, which subverted the traditional material design ideas and greatly broadened the composition design space of alloys. The high entropy effect, lattice distortion effect, slow diffusion effect and cocktail effect of high-entropy alloys make them have the potential to serve stably at high temperatures.
[0003] Traditional MB2-type boride-based ultra-high temperature ceramics, such as HfB2, ZrB2, TaB2, and TiB2, have a hexagonal structure and a crystal space group of P6 / mmm. They have a series of superior comprehensive properties, such as high melting point, high hardness, high strength, high thermal conductivity, and high thermal shock resistance. However, the strong covalent bonds in boride ceramics and the oxygen impurities contained in the powder have become the main bottlenecks restricting their sintering densification. At the same time, in practical applications, due to the poor oxidation resistance of boride ceramics, their widespread use in extreme environments is also limited.
[0004] Changing the composition of alloying elements, such as by adding trace elements and replacing different elements, is an effective way to improve material properties. Therefore, in the field of high entropy alloys, how to adjust the alloy composition and ratio to improve the mechanical properties of the alloy has become a technical problem that needs to be solved urgently. Therefore, in the field of high entropy alloys, how to adjust the alloy composition and ratio to improve the mechanical properties of the alloy has become a technical problem that needs to be solved urgently. Summary of the invention
[0005] In view of the above technical problems, the present invention provides a high-strength M2B type high entropy alloyed boride ceramic and a preparation method thereof. The present invention obtains a single M2B type high entropy alloyed boride ceramic by adjusting the gold composition and ratio of the high entropy alloyed boride ceramic, thereby improving the density, oxidation resistance and mechanical properties of the alloy.
[0006] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a high-strength M2B type high-entropy alloyed boride ceramic, comprising the following elements Fe, Co, Ni, Cr, and B, the atomic ratio of which is 1.0:1.0:1.0:1.0:2.0, and the high-strength M2B type high-entropy alloyed boride ceramic is composed of a tetragonal phase M2B, M is Fe, Co, Ni and Cr, and the atomic ratio of Fe, Co, Ni and Cr is 1:1:1:1.
[0007] The present invention selects transition metal elements (Cr, Fe, Co, Ni) with similar physical and chemical properties, the absolute value of the mixing enthalpy between the B element and the Co, Cr, Fe, Ni elements is large, and there is a large electronegativity difference between B and other elements, B-Co, B-Cr, B-Fe and B-Ni undergo a eutectic reaction to obtain a stable boride phase.
[0008] The M2B tetragonal phase is a rod-like structure.
[0009] A method for preparing high-strength M2B type high entropy alloyed boride ceramics comprises the following steps:
[0010] (1) Weighing boron powder and powdered iron, cobalt, nickel and chromium, uniformly mixing them and then pressurizing them to obtain a green body;
[0011] (2) placing the blank into a vacuum arc melting furnace and evacuating the vacuum, then introducing a protective gas, using a tungsten needle current to strike the arc, increasing the current until the alloy elements melt into a liquid state, maintaining the current for 180s to 240s, then turning off the current, and obtaining an ingot after cooling;
[0012] (3) Turn the ingot over and repeat step (2) to obtain a high-strength M2B-type high-entropy alloyed boride ceramic.
[0013] As a preferred embodiment of the present invention, the boron powder and powdered iron, cobalt, nickel and chromium have a purity of 99.95% and a particle size of 200 meshes.
[0014] As a preferred embodiment of the present invention, in the step (1), the pressure of the pressurization treatment is 10 MPa and the time is 3 minutes.
[0015] As a preferred embodiment of the present invention, in the step (2), the pressure after vacuuming is 0.003Pa-0.005Pa; the introduction of protective gas is stopped after the pressure reaches half the atmospheric pressure, and the vacuuming and introduction of protective gas are repeated 2-3 times.
[0016] As a preferred embodiment of the present invention, in the step (2), when the tungsten needle current is used to strike the arc, the tungsten needle is moved to 1 to 3 mm above the blank, and the arc is struck with a current of 20 to 30 A.
[0017] As a preferred embodiment of the present invention, in step (3), the remelting is performed by repeatedly turning over and repeating step (2) 10-15 times.
[0018] As a preferred embodiment of the present invention, the maximum current is maintained for 3-4 minutes during the remelting process.
[0019] As a preferred embodiment of the present invention, the remelted ingot is subjected to surface treatment and drying treatment to obtain a high-strength M2B type high-entropy alloyed boride ceramic.
[0020] The surface treatment specifically includes: cutting the remelted ingot, polishing the surface to make it bright, and cleaning it with anhydrous ethanol.
[0021] The drying treatment specifically includes drying the surface treated ingot at a vacuum degree of 3Pa to 5Pa and a temperature of 100°C to 120°C for 15 to 20 minutes.
[0022] As a preferred embodiment of the present invention, before arc melting in step (3), the chamber of the vacuum arc melting furnace is cleaned and rinsed with anhydrous ethanol.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) Due to the existence of high mixing entropy effect and lattice distortion effect, the M2B-type high-strength high-entropy alloyed boride ceramics described in the present invention are composed of a single tetragonal phase M2B, including Co, Cr, Fe, Ni and B elements, and therefore have high-temperature oxidation resistance, compactness and excellent mechanical properties.
[0025] (2) The present invention prepares a single M2B type high-strength high-entropy alloyed boride ceramic with uniform and controllable composition for the first time by vacuum arc melting and matching the chemical composition and content of high-entropy alloyed boride ceramics. This avoids the generation of impurities due to factors such as sintering process limitations or the introduction of other impurities, resulting in more pores and insufficient density in the obtained samples, which leads to a sharp decrease in the hardness, modulus and fracture toughness of the samples. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the XRD pattern of the high-strength M2B-type high-entropy alloyed boride ceramic prepared in Example 1 of the present invention.
[0027] Figure 2 This is a microstructure morphology of the high-strength M2B type high-entropy alloyed boride ceramic prepared in Example 1 of the present invention.
[0028] Figure 3 This is a two-dimensional hardness distribution diagram of the high-strength M2B type high-entropy alloyed boride ceramic prepared in Example 1 of the present invention.
[0029] Figure 4 This is a two-dimensional distribution diagram of the Young's modulus of the high-strength M2B-type high-entropy alloyed boride ceramic prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0031] Example 1
[0032] The preparation method of the high-strength M2B type high entropy alloyed boride ceramic comprises the following steps:
[0033] Step 1: According to the atomic ratio of Fe, Co, Ni, Cr, and B of 1.0:1.0:1.0:1.0:2.0, the reaction raw materials are weighed: 8.3775g of iron powder, 8.8395g of cobalt powder, 8.8035g of nickel powder, 7.8000g of chromium powder, and 3.2430g of boron powder. The purity of the powders used is 99.95%, and the particle size is 200 mesh. The raw materials are mixed evenly, and then a round cake-shaped blank is obtained by using a Shenyang Kejing tablet press with a pressure of 10MPa and a tablet pressing time of 3 minutes.
[0034] Step 2: First, place the pressed round cake-shaped blank into the auxiliary melting pool of the water-cooled copper crucible mold of the vacuum arc melting furnace, close the furnace door, and then turn on the vacuum pump to evacuate the air in the furnace body, so that the pressure in the furnace is reduced to 0.003Pa, and then turn off the vacuum pump; then introduce argon gas to make the input argon gas reach half the atmospheric pressure, close the argon valve, and repeat twice to clean the vacuum chamber. When the smelting starts, move the tungsten needle to 1mm above the blank, strike the arc with a current of 20A, and the melting current begins to increase slowly. The temperature is controlled at 2200℃, so that the remaining alloy elements melt into liquid, stay for 180s and then turn off the current, and get the ingot after cooling.
[0035] Step 3: Use the method in step 2 to turn the ingot over and remelt it, and turn it over and remelt it 10 times to obtain a remelted ingot; wait for the remelted ingot to cool down, open the vent valve to balance the internal and external pressures, and open the furnace door to take samples.
[0036] Step 4: After cutting the remelted ingot, polish the surface to make it bright, and clean it with anhydrous ethanol; then dry it at a vacuum degree of 5 Pa and a temperature of 120°C for 20 minutes to obtain a high-strength M2B-type high-entropy alloyed boride ceramic.
[0037] Example 2
[0038] The preparation method of the high-strength M2B type high entropy alloyed boride ceramic comprises the following steps:
[0039] Step 1: According to the atomic ratio of Fe, Co, Ni, Cr, and B of 1.0:1.0:1.0:1.0:2.0, the reaction raw materials are weighed: 8.3775g of iron powder, 8.8395g of cobalt powder, 8.8035g of nickel powder, 7.8000g of chromium powder, and 3.2430g of boron powder. The purity of the powders used is 99.95%, and the particle size is 200 mesh. The raw materials are mixed evenly, and then a round cake-shaped blank is obtained by using a Shenyang Kejing tablet press with a pressure of 10MPa and a tablet pressing time of 3 minutes.
[0040] Step 2: First, place the pressed round cake-shaped blank into the auxiliary melting pool of the water-cooled copper crucible mold of the vacuum arc melting furnace, close the furnace door, and then turn on the vacuum pump to evacuate the air in the furnace body, so that the pressure in the furnace is reduced to 0.005Pa, and then turn off the vacuum pump; then introduce argon gas to make the input argon gas reach half the atmospheric pressure, close the argon valve, and repeat 3 times to clean the vacuum chamber. When the smelting starts, move the tungsten needle to 3mm above the blank, strike the arc with a current of 30A, and the melting current begins to increase slowly. The temperature is controlled at 2200℃, so that the remaining alloy elements melt into liquid, stay for 240s and then turn off the current, and get the ingot after cooling.
[0041] Step 3: Use the method in step 2 to turn the ingot over and remelt it, and turn it over and remelt it 15 times to obtain a remelted ingot; wait for the remelted ingot to cool down, open the vent valve to balance the internal and external pressures, and open the furnace door to take samples.
[0042] Step 4: After the remelted ingot is cut, the surface is polished to make it bright and cleaned with anhydrous ethanol; then it is dried at a vacuum degree of 3 Pa and a temperature of 100°C for 15 minutes to obtain a high-strength M2B-type high-entropy alloyed boride ceramic.
[0043] Comparative Example 1
[0044] The only difference between the preparation method of the high-strength and high-entropy alloyed boride ceramics described in this comparative example and that in Example 1 is that the reaction raw materials are weighed according to the atomic ratio of Fe, Co, Ni, Cr, and B of 1.2:1.2:1.2:1.2:1.6: 8.3775 g of iron powder, 8.8395 g of cobalt powder, 8.8035 g of nickel powder, 7.8000 g of chromium powder, and 2.1622 g of boron powder.
[0045] Comparative Example 2
[0046] The only difference between the preparation method of the high-strength and high-entropy alloyed boride ceramics described in this comparative example and that in Example 1 is that the reaction raw materials are weighed according to the atomic ratio of Fe, Co, Ni, Cr, and B of 1.0:1.0:1.0:1.0:1.0:1.0: 8.3775 g of iron powder, 8.8395 g of cobalt powder, 8.8035 g of nickel powder, 7.8000 g of chromium powder, and 1.6215 g of boron powder.
[0047] Comparative Example 3
[0048] The preparation method of the high-strength M2B type high entropy alloyed boride ceramic comprises the following steps:
[0049] Step 1: According to the atomic ratio of Fe, Co, Ni, Cr, and B of 1.0:1.0:1.0:1.0:2.0, weigh the reaction raw materials: 8.3775g of iron powder, 8.8395g of cobalt powder, 8.8035g of nickel powder, 7.8000g of chromium powder, and 3.2430g of boron powder. The purity of the powders used is 99.95%, and the particle size is 200 mesh.
[0050] Step 2: The powder was loaded into a graphite mold with an inner diameter of 30 mm. Hot pressing sintering was performed in a graphite heating furnace, and a pressure of 35 MPa was applied for 2 minutes before heating. The furnace was then evacuated and heated at a heating rate of 600 ° C / hour. After the furnace temperature reached about 1400 ° C, argon was backfilled. When the furnace temperature reached 2000 ° C, a pressure of about 35 MPa was applied during the holding period. The sintering time was maintained at 2000 ° C for 1 hour. The furnace was cooled to 1200 ° C at a cooling rate of 600 ° C / hour, and then naturally cooled to room temperature to obtain a block sample through a solid-state reaction.
[0051] Step 3: Polish the surface of the sample obtained by hot pressing to make it bright, and clean it with anhydrous ethanol; then dry it at a vacuum degree of 5 Pa and a temperature of 120°C for 20 minutes to obtain an M2B type high entropy alloy.
[0052] Comparative Example 4
[0053] The preparation method of the high-strength M2B type high entropy alloy comprises the following steps:
[0054] Step 1: According to the atomic ratio of Fe, Co, Ni, Cr, and B of 1.0:1.0:1.0:1.0:2.0, weigh the reaction raw materials: 8.3775g of iron powder, 8.8395g of cobalt powder, 8.8035g of nickel powder, 7.8000g of chromium powder, and 3.2430g of boron powder. The purity of the powders used is 99.95%, and the particle size is 200 mesh.
[0055] Step 2: The uniformly mixed powders were sintered by spark plasma sintering at 25 MPa and maintained for 10 min. The sample was sintered at 2000 °C to obtain a bulk sample through a solid-state reaction.
[0056] Step 3: Polish the surface of the sample obtained by spark plasma sintering to make it bright, and clean it with anhydrous ethanol; then dry it at a vacuum degree of 5 Pa and a temperature of 120°C for 20 minutes to obtain a high-strength M2B-type high-entropy alloy.
[0057] Comparative Example 5
[0058] The only difference between the preparation method of the high-strength M2B type high-entropy alloyed boride ceramic and Example 1 is that in step 2, the arc striking current is 40A, the melting current starts to increase slowly, and the temperature is controlled at 3000°C so that the remaining alloy elements melt into liquid state, and the current is turned off after staying for 360s.
[0059] Effect example
[0060] The hardness, Young's modulus, density and high temperature oxidation resistance of the high entropy alloyed boride ceramics obtained in the test examples and comparative examples are shown in Table 1.
[0061] The density, hardness, Young's modulus and toughness of the (Cr, Fe, Co, Ni)2B medium-entropy alloy obtained in the embodiment and the comparative example were tested by an Archimedean balance, a digital Vickers hardness tester, a nanoindenter and a fully automatic micro Vickers hardness tester.
[0062] Table 1
[0063]
[0064] According to Table 1, the hardness, Young's modulus, compactness and fracture toughness of the high-strength M2B high-entropy alloyed boride ceramics prepared in Example 1-2 are much higher than those in Comparative Example 1-4. It can be known from the results of XRD that: ① The pure phase body-centered tetragonal phase sample prepared by arc melting in the present invention is determined by the space group of PDF, Fe2B (89-1993), Co2B (89-1994), Ni2B (89-1995), Cr2B (89-89-4876), the space group is I4 / mcm, which is a body-centered tetragonal structure, and the body-centered tetragonal phase has good toughness. ② Only one set of diffraction peaks appears. Due to the incorporation of large-radius atoms, lattice distortion is generated. The lattice distortion effect will hinder the dislocation movement between the lattices, produce solid solution strengthening, and improve the hardness and strength of the sample.
[0065] According to the embodiment and comparative examples 1-2, under the combined effect of the sintering process and the stoichiometric ratio, due to the high entropy effect and the cocktail effect, according to the binary alloy phase diagram, when the stoichiometric ratio M:C is 2:1, a pure phase M2B high entropy ceramic can be generated, which is a body-centered tetragonal phase. When the stoichiometric ratio M:C is 3:1 or 4:1, a mixture of a body-centered tetragonal phase M2B and a face-centered cubic phase is generated, and the phase precipitation rule is that the solid solution phase M2B phase precipitates first. Due to the supersaturation of the body-centered tetragonal phase, the transition metal generates a face-centered cubic phase due to the larger stoichiometric ratio.
[0066] It can be seen from Example 1 and Comparative Examples 3-4 that hot pressing sintering and spark plasma sintering cannot obtain pure phase M2B due to the sintering temperature or the introduction of carbon elements in the graphite mold. The obtained samples have more pores, insufficient density, and produce impure phases, resulting in a sharp decrease in the hardness, modulus and fracture toughness of the samples. In the XRD results of hot pressing sintering and spark plasma sintering, carbide impure phases and face-centered cubic phases synthesized by transition metals appeared. Due to the introduction of carbon elements and the formation of face-centered cubic phases, the various properties of Comparative Examples 3-4 dropped sharply. High entropy boride ceramics are generally synthesized by spark plasma sintering, hot pressing sintering, spreading high temperature reaction and boron / carbon thermal reduction reaction. The obtained samples have low density, and due to the limitations of the sintering process (sintering temperature) and the introduction of other impurities, it is difficult to obtain pure phase M2B boride ceramics.
[0067] Comparative Example 5 Compared with Example 1, the present invention adopts arc melting as the preparation method because the instantaneous temperature of arc melting can reach about 2200°C, which meets the synthesis temperature of high entropy boride and can obtain the solid solution of boride in a very short time. However, in Comparative Example 5, the arc current is too large, which will lead to too high instantaneous temperature. Due to the strong thermal shock, the sample has a temperature gradient with too large temperature difference, resulting in cracks and even fractures, which will affect the density of the sample and produce more defects, thereby affecting the mechanical properties of the sample.
[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A high-strength M2B type high-entropy alloyed boride ceramic, characterized in that: The high-strength M2B-type high-entropy alloyed boride ceramic is composed of the following elements: Fe, Co, Ni, Cr, and B, and the atomic ratio of the elements is 1.0:1.0:1.0:1.0:2.0; the high-strength M2B-type high-entropy alloyed boride ceramic is composed of an M2B tetragonal phase, M is Fe, Co, Ni, and Cr, and the atomic ratio of Fe, Co, Ni, and Cr is 1:1:1:1; The preparation method of the high-strength M2B type high-entropy alloyed boride ceramic comprises the following steps: (1) Weighing boron powder, iron powder, cobalt powder, nickel powder and chromium powder, uniformly mixing and then pressurizing to obtain a green body; (2) placing the blank into a vacuum arc melting furnace and evacuating the vacuum, then introducing a protective gas, using a tungsten needle current to strike the arc, increasing the current until the alloy elements melt into a liquid state, maintaining the current for 180s to 240s, then turning off the current, and obtaining an ingot after cooling; (3) Turn the ingot over and repeat step (2) to obtain a high-strength M2B-type entropy alloyed boride ceramic.
2. The high-strength M2B type high-entropy alloyed boride ceramic according to claim 1, characterized in that: The boron powder, iron powder, cobalt powder, nickel powder and chromium powder have a purity of 99.95% and a particle size of 200 meshes.
3. The high-strength M2B type high-entropy alloyed boride ceramic according to claim 1, characterized in that: In the step (1), the pressure of the pressurization treatment is 10 MPa and the time is 3 minutes.
4. The high-strength M2B type high-entropy alloyed boride ceramic according to claim 1, characterized in that: In the step (2), the pressure after vacuuming is 0.003Pa-0.005Pa; the introduction of protective gas is stopped after the pressure reaches half the atmospheric pressure, and the vacuuming and introduction of protective gas are repeated 2-3 times.
5. The high-strength M2B type high entropy alloyed boride ceramic according to claim 1, characterized in that: In the step (2), when the tungsten needle current is used to strike the arc, the tungsten needle is moved to 1 to 3 mm above the blank, and the arc is struck with a current of 20 to 30 A.
6. The high-strength M2B type high-entropy alloyed boride ceramic according to claim 1, characterized in that: In the step (3), the mixture is turned over and step (2) is repeated 10-15 times for remelting.
7. The high-strength M2B type high entropy alloyed boride ceramic according to claim 1, characterized in that: The remelted ingot is subjected to surface treatment and drying treatment to obtain high-strength M2B type high entropy alloyed boride ceramics.
8. The high-strength M2B type high entropy alloyed boride ceramic according to claim 7, characterized in that: The surface treatment specifically includes: cutting the remelted ingot, grinding the surface to make it bright, and cleaning it with anhydrous ethanol; The drying treatment is specifically as follows: drying the surface treated ingot at a vacuum degree of 3Pa to 5Pa and a temperature of 100°C to 120°C for 15 to 20 minutes.